Influence of Teacher Training on Technology Integration in Learning Media Development: Pengaruh Pelatihan Guru terhadap Integrasi Teknologi dalam Pengembangan Media Pembelajaran - Sabariah, Sabariah; Rufi’i, Rufi’i; R, Retno Danu; Sitompul, Nurmida Chaterine; Elvianti, Elsa; Anas Sulaiman, Prema Karira; Al-Ayyubi, Salahuddin (STAI Publisistik Thawalib Jakarta, 2024)
In today’s digital era, enhancing teachers’ capacity to develop technology-based learning media is essential, as it directly impacts student engagement and learning outcomes. This study aims to examine the effect of coaching on high school teachers’ abilities to create technology-driven instructional materials. Using a one-group pretest-posttest design, data was collected from teachers who had completed training in educational media development. The sample, selected via purposive sampling, included high school educators in Surabaya, with data gathered through tests and observations assessing media quality and coaching effectiveness. Findings reveal a significant relationship between coaching quality and teachers' media development, with interactive presentations, mobile apps, and instructional videos being the most commonly created resources. The study identifies limited infrastructure and technical support as challenges to implementation. Novel insights from this research highlight the need for ongoing technical support and accessible resources to sustain media integration in classrooms. This study contributes to educational practices by providing evidence of effective coaching strategies and underscoring the importance of comprehensive support in fostering sustainable technology adoption among educators.